Effect of Storage of Placenta Tissue at –20°C on Properties of Its Aqueous and Saline Extracts - Nardid, Oleg A.; Rozanova, Ekaterina D.; Cherkashina, Yana O.; Repina, Svetlana V.; Nardid, Eduard O. (Problems of Cryobiology and Cryomedicine, 2014)
Research was aimed to study the effect of human placenta tissue storage at –20°C on the features of procured from it aqueous-saline extracts and their certain fractions. The methods of gel-chromatography, optical spectroscopy and spin probe EPR were used in the research. Spin probe EPR demonstrated the exposure of erythrocytes with fraction of human placenta extracts below 5 kDa as not affecting the microviscosity of erythrocyte cytosol. Along with that we observed the modification of temperature dependence of spin probe mobility under exposure with the same fraction of placenta extracts, stored for 6 months at –20°C. This correlated with a decrease in acid resistance of erythrocytes under the effect of this fraction. Probl Cryobiol Cryomed 2014; 24(1):28–37.